Religious Courts During the Ottoman Era - Sa’adah, Hidayatus (Maliki Interdisciplinary Journal, 2024)
During the Ottoman period, the judiciary was an important part of a highly organized government structure and reflected a blend of Islamic law (sharia) and local customary law. This judicial system is under the rule of the Sultan who acts as the main protector of law and justice. However, the day-to-day implementation is carried out by judicial officials, called Qadi. Qadi is responsible for resolving various disputes, ranging from family affairs, land, to criminal matters. The Ottoman judiciary refers to the Canon (secular law) drafted by the Sultan, as well as the sharia as the main moral and legal basis. Scholars have a great influence in interpreting Islamic law and giving fatwas as a guide for Qadi. The court structure consisted of various levels, from the local courts administered by the Qadi to the Supreme Court in the center of the empire.